Implementasi Kebijakan Pariwisata Berkelanjutan Studi di Tanjung Bongo, Kabupaten Halmahera Utara - Umasugi, Mohbir (Social and Political Science Faculty - Universitas Tidar, 2023)
The sustainable tourism approach is used as a guideline in developing tourism in the region. However, the construction of various tourist accommodations can disrupt the environment in tourist areas. The aim of the research is to analyze the implementation of sustainable tourism, especially in relation to the development of tourist accommodation. Direct observation in the Tanjung Bongo area as a form of observation and interviews with informants were used as primary data sources. Studying various documentation and tourism development documents in North Halmahera is a stage of collecting secondary data. This research found an interesting thing that the sustainable tourism concept implemented in Tanjung Bongo did not last long. Several supporting facilities experienced a decrease in carrying capacity due to lack of maintenance and tourist visits during Covid-19. Apart from that, the construction of tourist accommodation and waste from tourists can disturb the environment in Tanjung Bongo. So the research contributes to implementation studies that focus on addressing policy sustainability. This research also opens up space for other researchers to develop study models regarding the sustainability of policy implementation by local governments which so far has not been supported by efforts to maintain the programs being implemented.